Synthesis of eight stereoisomers of pochonicine: nanomolar inhibition of β-N-acetylhexosaminidases. - Zhu, J; Nakagawa, S; Chen, W; Adachi, I; Jia, Y; Hu, X; Fleet, G; Wilson, F; Nitoda, T; Horne, G; van Well, R; Kato, A; et al. (2013)
Pochonicine, the first naturally occurring polyhydroxylated pyrrolizidine containing an acetamidomethyl group, which was isolated from Pochonia suchlasporia var. suchlasporia TAMA 87, together with its enantiomer and their C-1 and/or C-3 epimers, have been synthesized from the sugar-derived cyclic nitrones 9D and 9L, respectively. An in-depth NMR study showed that both the (1)H and (13)C NMR spectra of the synthetic pochonicines (1D and 1L) matched very well with those of natural pochonicine in D2O, which unequivocally determined the relative configuration of the natural product as 1D or 1L. In addition, comparison of the optical rotations of the synthetic pochonicines and that of the natural product, but more convincingly their glycosidase inhibition profiles, confirmed the absolute configuration of natural pochonicine as 1R,3S,5R,6R,7S,7aR. Thereby, the structure of natural pochonicine was unequivocally determined as (+)-(1R,3S,5R,6R,7S,7aR)-pochonicine (1D). Glycosidase inhibition experiments showed that natural pochonicine 1D and its epimers 2D, 3D, and 4D all are powerful inhibitors of hexosaminidases (five β-N-acetylglucosaminidases and two β-N-acetylgalactosaminidases) while their enantiomers 1L, 2L, 3L, and 4L are much weaker inhibitors of the same enzymes. (-)-3-epi-Pochonicine (2L) was found to be a potent and selective inhibitor of α-l-rhamnosidase. None of the compounds showed any inhibition of α-GalNAcase.